Chiral Pesticides in Soil and Water and Exchange with the Atmosphere - Terry F. Bidleman; Andi D. Leone; Renee L. Falconer; Tom Harner; Liisa M.M. Jantunen; Karin Wiberg; Paul A. Helm; Miriam L. Diamond; Binh Loo (The Scientific World Journal)
The enantiomers of chiral pesticides are often metabolised at different rates in soil and water, leading to nonracemic residues. This paper reviews enantioselective metabolism of organochlorine pesticides (OCPs) in soil and water, and the use of enantiomers to follow transport and fate processes. Residues of chiral OCPs and their metabolites are frequently nonracemic in soil, although exceptions occur in which the OCPs are racemic. In soils where enantioselective degradation and/or metabolite formation has taken place, some OCPs usually show the same degradation preference — e.g., depletion of (+)trans-chlordane (TC) and (–)cis-chlordane (CC), and enrichment of the metabolite (+)heptachlor exo-epoxide (HEPX). The selectivity is ambivalent for other chemicals; preferential loss of either (+) or (–)o,p’-DDT and enrichment of either (+) or (–)oxychlordane (OXY) occurs in different soils. Nonracemic OCPs are found in air samples collected above soil which contains nonracemic residues. The enantiomer profiles of chlordanes in ambient air suggests that most chlordane in northern Alabama air comes from racemic sources (e.g., termiticide emissions), whereas a mixture of racemic and nonracemic (volatilisation from soil) sources supplies chlordane to air in the Great Lakes region. Chlordanes and HEPX are also nonracemic in arctic air, probably the result of soil emissions from lower latitudes. The (+) enantiomer of α-hexachlorocyclohexane (α-HCH) is preferentially metabolised in the Arctic Ocean, arctic lakes and watersheds, the North American Great Lakes, and the Baltic Sea. In some marine regions (the Bering and Chukchi Seas, parts of the North Sea) the preference is reversed and (–)α-HCH is depleted. Volatilisation from seas and large lakes can be traced by the appearance of nonracemic α-HCH in the air boundary layer above the water. Estimates of microbial degradation rates for α-HCH in the eastern Arctic Ocean and an arctic lake have been made from the enantiomer fractions (EFs) and mass balance in the water column. Apparent pseudo first-order rate constants in the eastern Arctic Ocean are 0.12 year-1 for (+)α-HCH, 0.030 year-1 for (–)α-HCH, and 0.037 year-1 for achiral Υ-HCH. These rate constants are 3–10 times greater than those for basic hydrolysis in seawater. Microbial breakdown may compete with advective outflow for long-term removal of HCHs from the Arctic Ocean. Rate constants estimated for the arctic lake are about 3–8 times greater than those in the ocean.